2016
DOI: 10.1186/s12917-016-0681-0
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genetic characterization of Piscirickettsia salmonis from Chilean and Canadian salmonids

Abstract: BackgroundThe study presents the phenotypic and genetic characterization of selected P. salmonis isolates from Atlantic salmon and rainbow trout suffering from SRS (salmonid rickettsial septicemia) in Chile and in Canada. The phenotypic characterization of the P. salmonis isolates were based on growth on different agar media (including a newly developed medium), different growth temperatures, antibiotics susceptibility and biochemical tests.ResultsThis is the first study differentiating Chilean P. salmonis iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 24 publications
4
47
0
Order By: Relevance
“…Specifically, the JC model was selected for the dnak gene, the JC+modelГ for efp , the T92 model for fumC , the K2 model for glyA , rpoD and trpB , and the HKY model for murG . Analysis using the BMCMC method returned a partial phylogeny for the P. salmonis strains; this phylogeny was consistent with previous reconstructions of P. salmonis strains isolated from Chilean salmonids (Nourdin‐Galindo et al, ; Otterlei et al, ; Saavedra et al, ). Phylogenetic reconstructions with individual and concatenated genes were congruent in separating the LF‐89 T and EM‐90 genogroups.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Specifically, the JC model was selected for the dnak gene, the JC+modelГ for efp , the T92 model for fumC , the K2 model for glyA , rpoD and trpB , and the HKY model for murG . Analysis using the BMCMC method returned a partial phylogeny for the P. salmonis strains; this phylogeny was consistent with previous reconstructions of P. salmonis strains isolated from Chilean salmonids (Nourdin‐Galindo et al, ; Otterlei et al, ; Saavedra et al, ). Phylogenetic reconstructions with individual and concatenated genes were congruent in separating the LF‐89 T and EM‐90 genogroups.…”
Section: Resultssupporting
confidence: 85%
“…In most cases, P. salmonis isolates die after a while, meaning that having “old” isolates is a highly complex and unlikely reality. Supporting this context, Otterlei et al () reported MLST sequence data for only 18 Chilean P. salmonis isolates, all of which were obtained from 2011 and 2012, primarily from just two geographical areas (i.e., Puerto Montt and East coast of Chiloe Island). The presently conducted analysis included the most ancient Chilean P. salmonis strain available (i.e., strain LF‐89 T ), which was isolated from O. kisutch in 1989.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to genetic distance, the separate grouping of the Chilean strains has also been correlated with a number of phenotypic features exhibited by EM‐90‐like and LF‐89 T ‐like strains (Otterlei et al., ; Saavedra et al., ). In the cited studies, the EM‐90‐like strains (matched cluster 2 in this study) showed differences in the optimal growth temperature on solid media, growth kinetics and host preference when compared to the LF‐89 T ‐like strains (matched cluster 1 in this study).…”
Section: Discussionmentioning
confidence: 99%
“…The reference strain LF‐89 (ATCC VR‐1361) was isolated for the first time in southern Chile in 1989, and since then, many new varieties have been isolated and characterized (Otterlei et al . ).…”
Section: Introductionmentioning
confidence: 97%